Systemic Sclerosis Presenting with Simultaneous Retinal Vasculitis in One Eye and Optic Neuritis in the other along with Severe Immune Haemolytic Anaemia - Avijit Moulick; Biswanath Sharma Sarkar; Anirban Jana; Pradipta Guha; Anjan Das (Journal of Clinical and Diagnostic Research, 2013)
Systemic Sclerosis (SSc) is a connective tissue disorder which involves multiple systems in a chronic progressive manner. Micro–angiopathic haemolytic anaemia is a distinguished feature of “scleroderma renal crisis”, which is manifested by severe hypertension, a rapidly progressing renal dysfunction and hyperreninaemia and is seen in patients with an early, diffuse form of the disease. A nervous system involvement is rare, though entrapment neuropathies have been reported. Who presented with a sequential loss of vision in both eyes; due to retinal vasculitis in right eye and optic nerve demyelination in the left eye. She also had severe Coombs’ negative haemolytic anaemia in absence of any renal dysfunction or hypertension. Both the ophthalmologic and the haematologic manifestations are very rare and both responded well to oral prednisolone therapy.